1998
DOI: 10.1002/clc.4960210210
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of atrial fibrillation and stroke in paced patients without prior atrial fibrillation: A prospective study

Abstract: SummaryBackground: Several reports suggest that the incidence of stroke and atrial fibrillation is reduced in patients receiving physiologic pacemakers, compared with patients receiving a venhicular pacemaker.Hvpothesis: The study was undertaken to address the impact of different pacing modalities on the incidence of stroke and atrial fibrillation.Methods: We prospectively analyzed 2 10 consecutive patients. Those with previous episodes of cerebral ischemia a n d or atrial fibrillation were excluded from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…clinical trials have established that atrial fibrillation (AF), which commonly occurs in patients with sinus node dysfunction (8,9), is associated with an annual risk of stroke of approximately 5%, which may be significantly lowered to 1.7% with appropriate anticoagulant therapy (10). Previous trials have suggested that physiologic pacing may decrease the incidence of AF (11)(12)(13)(14).…”
Section: See Page 1623mentioning
confidence: 99%
“…clinical trials have established that atrial fibrillation (AF), which commonly occurs in patients with sinus node dysfunction (8,9), is associated with an annual risk of stroke of approximately 5%, which may be significantly lowered to 1.7% with appropriate anticoagulant therapy (10). Previous trials have suggested that physiologic pacing may decrease the incidence of AF (11)(12)(13)(14).…”
Section: See Page 1623mentioning
confidence: 99%
“…[8][9][10] We set out to evaluate the association of statin therapy and the risk of developing AF in patients implanted with permanent pacemakers, a population with a high incidence of AF. [11][12][13] …”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is very common in patients with bradycardia undergoing cardiac pacemaker implantation (1)(2)(3)(4). Nonvalvular AF has been recognized as a cause of mortality (5) and in particular it has been associated to a five-fold increase in the risk of ischemic stroke, probably associated to atrioembolic mechanism (6 -9).…”
mentioning
confidence: 99%